Karakterisasi Sifat Toleransi terhadap Cekaman Kering Kacang Tanah (Arachis hypogega L.) Varietas Nasional pada Tahap Perkecambahan - Adisyahputra Adisyahputra; Settings Reni Indrayanti; Dwi Eldina (Jurnal Matematika Sains dan Teknologi, 2004)
The aim of this research is to determine character for drought tolerance character prediction of peanut national variety on germination phase using PEG 6000 solution. Preliminary test using drought tolerance genotipes (US 605 and US 693), susceptible genotipe (PI 409) conducted to evaluate appropriate concentration of PEG solution as drought treatment. PEG 10% is appropriate for drought treatment. Experiment using factorial random complete design with eight national varieties, Badak, Gajah, Jerapah, Kelinci, Komodo, Macan, Panther, Singa, and PEG solution. Minimum water uptake for germination is obtained from proportion between seedling weight to seed weight with seed weight. Root length, number of lateral root and seedling dry weight (without cotyledon) are counted on seventh day after germination. Seed germinated using UKDdp method. ANOVA two way for water uptake variable, ANOVA one way for root length and number of lateral root and seedling dry weight (without cotyledon) is used to analyze data, continue with DMRT and Pearson product moment correlation between minimum water uptake for germination and root length, seedling dry weight (without cotyledon). And Spearman correlation is used between minimum water uptakes for germination with number of lateral root. The results base on this research are, drought tolerance characterization of peanut national variety could evaluate on germination phase simulated by 10% PEG 6000 solution. (2) Minimum water uptake for peanut seed germination could be use as determine character to drought (3) Base on minimum water uptake for germination, Gajah and Panther grouped as drought tolerance varieties, Macan, Jerapah, Singa and Badak as medium tolerance varieties, and Komodo and kelinci as susceptible varieties.(4) In peanut, root length, number of lateral root and seedling dry weight (without cotyledon) can not be use as determine character to drought on germination phase.